Construcción experimental de un horno de leña mejorado para comparar su eficiencia con un horno de leña tradicional - Cabrera Moreno, Cristian Vicente (2019)
Research work proposes a way to improve the quality of products that are baked in wood ovens. Traditional fuelwood kilns at the time of burning firewood contaminate with ash and CO2 the product being cooked, which is why research has been planned on a new method of baking with firewood. An improved fuelwood oven has been proposed based on research carried out by universities in Argentina which create a drum oven. The research has 3 phases to be able to develop it completely: Phase 1: Research was conducted on the optimal materials for the construction of furnaces and materials required for food handling. Phase 2: construction of the new improved fuelwood oven. Phase 3: Measurements of the temperature of the improved fuelwood oven were taken to compare them with the measurements taken in the traditional fuelwood oven.